The Cost of Human Exceptionalism: Review of Pamela Newkirk, Spectacle: The Astonishing Life of Ota Benga - Sax, Boria (Humanimalia, 2015)
Pamela Newkirk. Spectacle: The Astonishing Life of Ota Benga. New York: HarperCollins, 2015. 336 pp. $14.84 hc.